Movement and diving behavior of satellite-tagged male sperm whales in the Gulf of Alaska - Wild, Lauren A.; Mueter, Franz J.; Straley, Jan M.; Andrews, Russ D. (Frontiers in Marine Science, 2024)
Male sperm whales (Physeter macrocephalus) are known to interact with and depredate from commercial longline fishing vessels targeting sablefish (Anoplopoma fimbria) in the Gulf of Alaska (GOA). This study aims to better understand their movement patterns and diving behavior in this region, and in relation to depredation behavior. Between 2007 and 2016 a total of 33 satellite tags were deployed on sperm whales interacting with fishing vessels in the eastern GOA. A subset of these tags also collected dive characteristics. We used state space models to interpolate hourly positions from tags and estimate behavioral state from 29 usable tag records, 14 of which had associated dive information. Whales exhibited slower horizontal movement (1.4 km/hr) within GOA waters compared to south of the GOA (5.5 km/hr), indicating tagged whales sped up when they left the region. Behavioral states indicated primarily foraging behavior (82% of locations) in the GOA and primarily transiting behavior (74% of locations) when whales left the GOA. Dive data showed average (±Standard Deviation) maximum dive depths of 396 m (±166), and dive durations of 32 min (± 9). Generalized additive models indicated that dives were significantly deeper and longer during the daytime than dawn, dusk, or nighttime, and dives were significantly deeper and shorter during quarter moons, when tidal currents are weakest. Maximum dive depth decreased in areas of higher sablefish CPUE, suggesting a potential link between the sablefish fishery and depredation behavior. As seafloor depth increased, up to 800 m, dives became deeper, indicating that whales were likely targeting both bathypelagic and mesopelagic prey. This highlights the importance of the GOA continental slope as a foraging ground for male sperm whales. This enhanced understanding of sperm whale foraging ecology informs management and conservation efforts in high latitude foraging grounds.